The reasons for the spatial and media distribution variations of ARGs in a typical semi-enclosed bay. (February 2023) - Shu, Qin; Li, Ruijing; Zhang, Haibo; Wang, Lisha; Guan, Qingtao; Wei, Guangke; Xu, Yunfeng; Jin, Shuaichen; Gao, Hui; Na, Guangshui
Abstract: Antibiotic resistance genes (ARGs) are considered a newly emerging contaminant. This study aimed to investigate the spatial and media distribution patterns of ARGs in Jiaozhou Bay, as well as the reasons behind these patterns. The results revealed that aminoglycoside and MLSB resistant genes predominated in all samples, and the relative abundance of ARGs ranging from 10 −6 to 10 −2, 10 −6 to 10 −3 and 10 −5 to 10 −2 copies/16S rRNA in coastal water, bay water, and sediments, respectively. The significant spatial variation of ARGs was explained by the fact that the coastal water was more susceptible to human activities, whereas environmental physicochemical factors played a crucial role in the bay water. The intrinsic reason for the media distribution variation was the different assembly processes in the two media, while the external reason was that the ARGs in the water and sediments were mainly influenced by environmental physicochemical factors and heavy metals, respectively. Highlights: The abundance of 54 ARGs applicable to the marine environment was quantified. The ARGs showed significant spatial and media variations in Jiaozhou Bay. The effects of human activities on ARGs decreased along the coast to the bay. Physicochemical factors and heavy metals explained the media variations of ARGs.